PENERAPAN BUSINESS INTELLIGENCE DASHBOARD DAN FORECASTING PADA JUMLAH PASIEN PUSKESMAS XYZ - Islamita Putri, Fadhilla; Suryamen, Haris; Mega Wahyuni, Ullya (Innotech: Jurnal Ilmu Komputer, Sistem Informasi dan Teknologi Informasi, 2024)
Public Health Center (Puskesmas) is a community health center that facilitates health services and implements community health efforts. In supporting its activities, the health center has not provided reports displaying visualizations according to the needs of the health center. Facing an increase in the number of patient visits, data analysis is needed to identify trends and forecast future patient visits. With more accurate information, the health center can plan and make better decisions in managing public health. To meet these needs, the proposed solution is the use of a dashboard-based system. Additionally, dashboards can play a crucial role in planning more effective disease awareness programs. By utilizing historical data and appropriate forecasting models, the health center can predict the number of patient visits and disease trends in the future. This will help the health center plan more effective prevention and intervention programs and improve the quality of patient care. In this study, data collection methods include field studies and literature reviews, with field studies involving observations and interviews. The research results include four dashboards: visit dashboard, polyclinic dashboard, disease case dashboard, and prediction dashboard.